To describe our nationality in the appearance of clothing based on the assortment of local national fabrics and the combination of colors - Satvaldiyeva Zarifa Alimzhanovna; Nabidzhanova Nargiza; Babayeva Shokxista Hamidxon Qizi (Genius Publishing Group, 2023)
In the article, dresses were created that reflected the external appearance of our magnificent buildings that Madden our nationality and were blurred in the “corel draw” program. For the selected model, the requirements for the item were developed. Based on the concept, a creative source was selected, and based on it, a collection of dresses was created.
Keywords: National fabrics; adras; xonatlas; leather